1970
DOI: 10.1126/science.167.3926.1740
|View full text |Cite
|
Sign up to set email alerts
|

Habituation and Dishabituation of the Gill-Withdrawal Reflex in Aplysia

Abstract: A behavioral reflex mediated by identified motor neurons in the abdominal ganglion of Aplysia undergoes two simple forms of shortterm modification. When the gill-with-drawal reflex was repeatedly evoked by a tactile stimulus to the siphon or mantle shelf, the amplitude of the response showed marked decrement (habituation). After a period of rest the response showed spontaneous recovery. The amplitude of a habituated response was facilitated by the presentation of a strong tactile stimulus to another part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
209
1
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(214 citation statements)
references
References 10 publications
3
209
1
1
Order By: Relevance
“…The gill-withdrawal reflex studied in Aplysia is a classic example of the habituation (desensitization) of reflex in response to repeated non-noxious stimuli [6][7][8]. Intuitively, this adaptation corresponds to the interpretation that since the sea slug is constantly bombarded with stimuli from sea waves, those harmless stimuli can be ignored if they do not represent potential threats to the animal.…”
Section: Gill-withdrawal Reflex As An Examplementioning
confidence: 99%
“…The gill-withdrawal reflex studied in Aplysia is a classic example of the habituation (desensitization) of reflex in response to repeated non-noxious stimuli [6][7][8]. Intuitively, this adaptation corresponds to the interpretation that since the sea slug is constantly bombarded with stimuli from sea waves, those harmless stimuli can be ignored if they do not represent potential threats to the animal.…”
Section: Gill-withdrawal Reflex As An Examplementioning
confidence: 99%
“…It should be possible to answer this question by comparing the neural mechanisms of the different forms of learning, ideally in the same preparation. The gill-and siphon-withdrawal reflex of Aplysia has been useful for such studies, because it exhibits several forms of learning including habituation, dishabituation, sensitization, and classical conditioning (Pinsker et al, 1970;Carew et al, 1971Carew et al, , 1981, and it is amenable to cellular analysis. Studies of the cellular mechanisms of learning in Aplysia have revealed both similarities and differences between the mechanisms contributing to dishabituation and sensitization (Carew et al, 1971;Wright et al, 1991;Cohen et al, 1997;Antonov et al, 1999) and also between those contributing to sensitization and classical conditioning (Hawkins et al, 1993;Antonov et al, 2001Antonov et al, , 2003Li et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…After locating the neurons and synapses involved in a simple conditioned reflex, the gill withdrawal reflex (Pinsker et al, 1970), the Kandel group was able to extend the Aplysia work to learning and succeeded, over a number of years, in mapping out the detailed synaptic events of learning and memory at the molecular level. Significantly, the results obtained on Aplysia have been found to carry over to higher animals remarkably well (Kandel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%